2021
DOI: 10.1159/000514921
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Serosal Perfusion Assessment during Colorectal Resection Using Visible Light Spectroscopy

Abstract: <b><i>Introduction:</i></b> Anastomotic leakage (AL) in colorectal surgery occurs with an incidence of up to 20%. Bowel perfusion is deemed to be one of the most important factors for anastomotic healing. However, not much is known about its variability during colorectal surgery and its impact on the outcome. Therefore, this study aims to evaluate serosal oxygen saturation patterns during colorectal resections with visible light spectroscopy (VLS). <b><i>Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Recently, several techniques, such as oxygen spectrometry, laser speckle imaging, thermography, and handheld vital microscopy, have been developed to evaluate intestinal perfusion [23][24][25][26]. However, these techniques are not yet widely used due to their high cost and technical complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several techniques, such as oxygen spectrometry, laser speckle imaging, thermography, and handheld vital microscopy, have been developed to evaluate intestinal perfusion [23][24][25][26]. However, these techniques are not yet widely used due to their high cost and technical complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Karliczek et al reported that the clinical judgment of surgeons appeared to have low sensitivity and specificity in predicting anastomotic leakage in colorectal anastomoses [22]. Recently, several techniques, such as oxygen spectrometry, laser speckle imaging, thermography, and handheld vital microscopy, have been developed to evaluate intestinal perfusion [23][24][25][26]. However, these techniques are not yet widely used due to their high cost and technical complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Grafitsch [40] explored visible light spectroscopy (VLS) to evaluate serosal oxygen saturation patterns during colorectal resections. The employed materials and methods included the use of VLS on the colonic serosa and evaluation of the bowel perfusion of patients undergoing left-sided colorectal resections at various times during surgery.…”
Section: Recto-colonic Perfusionmentioning
confidence: 99%